Penguatan Literasi Digital melalui Sosialisasi dan Pengembangan Platform Pengaduan Cyberbullying di SMP Negeri 9 Denpasar - Helmy Syakh Alam; Eka Grana Aristyana Dewi; Elok Ratna Galih; Flowrencio Bintang Sangjaya; I Putu Manik Sedana Putra; Pande Komang Surya Adnyana; Putu Enda Abdi Permana (Yayasan Kawanad, 2026)
The widespread use of social media among junior high school students has heightened exposure to cyberbullying and weakened awareness of responsible digital behavior. This community service program was designed to strengthen digital literacy and establish an accessible reporting channel at SMP Negeri 9 Denpasar. Program activities included exploratory needs-assessment interviews, interactive socialization sessions, website development, and a post-session evaluation using a 25-item digital quiz. A total of 34 students participated, with 33 valid responses retained for analysis. Quiz results yielded a mean accuracy score of 72.23%, with individual scores ranging from 36% to 96%. The majority of participants (63%) scored above 70%, reflecting a satisfactory level of conceptual understanding, although situational and ethics-based questions proved considerably more challenging. The developed website serves as an educational repository and a WhatsApp-based reporting channel for cyberbullying cases. Long-term monitoring remains necessary to assess the platform's sustained effectiveness in supporting students' digital literacy development.